2017
DOI: 10.1111/1755-5922.12312
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin (BH4): Targeting endothelial nitric oxide synthase as a potential therapy for pulmonary hypertension

Abstract: Summary Purpose Pulmonary Hypertension (PH) is complex disease which is associated with endothelial and cardiac dysfunction. Tetrahydrobiopterin (BH4) regulates endothelial nitric oxide synthase (eNOS) to produce nitric oxide rather than superoxide which maintains normal endothelial and cardiac function. This study explores the therapeutic potential of BH4 in experimental PH. Methods Monocrotaline‐induced PH in rats and Hph‐1 deficiency in mice were used for animal experiments. Hemodynamic measurements using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Increased ROS, an altered redox state and elevated oxidant stress have been indicated in the lung and RV of various PAH animal models, in addition to MCT toxicity (60). Furthermore, a more recent study revealed that a deficiency in tetrahydrobiopterin, an essential cofactor for eNOS coupling, may be associated with MCT-induced PAH rats (61). In addition, SR59230A may inhibit inflammatory infiltration in the perivascular and peribronchial regions, whereas inflammatory cell recruitment has been known to accelerate the accumulation of ROS and lung functional impairment (62).…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS, an altered redox state and elevated oxidant stress have been indicated in the lung and RV of various PAH animal models, in addition to MCT toxicity (60). Furthermore, a more recent study revealed that a deficiency in tetrahydrobiopterin, an essential cofactor for eNOS coupling, may be associated with MCT-induced PAH rats (61). In addition, SR59230A may inhibit inflammatory infiltration in the perivascular and peribronchial regions, whereas inflammatory cell recruitment has been known to accelerate the accumulation of ROS and lung functional impairment (62).…”
Section: Discussionmentioning
confidence: 99%
“…While drugs that inhibit the degradation of cGMP are not usually used in patients with hypertension, they can be utilized in pulmonary arterial hypertension, such as the phosphodiesterase inhibitors sildenafil and tadalafil [ 50 ]. An impaired NO pathway is frequently associated with the development of this disease through different mechanisms, including pulmonary endothelial dysfunction, reduced NOS3 activity, decreased expression of the bone morphogenetic protein receptor II (BMPRII), increased symmetric and asymmetric dimethylarginine (ADMA) levels or arginase I, and tetrahydrobiopterin (BH4; a cofactor involved in NOS activity) or arginine deficiency [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Deficiency In No Bioavailability and Activity In Cardiovascu...mentioning
confidence: 99%
“…The bioavailability of nitric oxide (NO) can be influenced by various factors that impact the activity of the standard NO synthesis pathway, carried out by nitric oxide synthases (NOSs). These factors include reduced levels of its substrate, arginine, or its cofactor tetrahydrobiopterin (BH4), and increased expression of arginase and levels of asymmetric dimethylarginine (ADMA), which competes with arginine for interaction with the enzyme [ 31 , 32 , 33 , 34 , 35 ]. Drugs that inhibit enzymes with nitrite reductase activity, such as xanthine oxidoreductase (XOR), can affect NO, as seen with febuxostat and allopurinol, which may inhibit nitrite-derived NO formation [ 36 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, interdomain electron transfer from NADPH of the reductase domain to the oxygenase domain appears to be slow. Therefore, eNOS uses BH 4 cofactor as an electron donor to rapidly reduce the oxyferrous complex, which can dissociate to ferric heme and superoxide in BH 4 -depleted condition [32][33][34]. In addition, this BH 4 has been shown to play a role of "redox switch" which means that it can attenuate superoxide release and promote the formation of NO; and that an addition of 7,8-BH 2 or sepiapterin enhances superoxide release while inhibiting the production of NO [35,36].…”
Section: Enos Dimerization and Uncouplingmentioning
confidence: 99%